PENINGKATAN MINAT DAN KETRAMPILAN BERCERITA WAYANG PADA PEMBELAJARAN BAHASA JAWA DENGAN PENGGUNAAN ALAT PERAGA WAYANG KULIT PADA SISWA KELAS VI SDN PANGONAN 02 TAHUN PELAJARAN 2015/2016 - Sutiah . (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2017)
This study started from the condition of students of class VI SDN Pangonan 02 are less interested and less trampilbercerita puppet in the Java language, aftermonitoring found several factors that cause, among the causes of it are, (1) Learning theJava language monotonous (2) Students are less interested the puppet story (3) theteacher does not use props puppet in this bercerita.Penelitian aims to determine theincrease in the interest and skills of storytelling puppets in class VI SDN Pangonan 022015/2016 academic year in the Java language learning after using props puppetkulit.Metode this research is action research (action research) are implemented in twocycles. And each cycle using phases: planning, implementation, observation, andrefleksi.Berdasarkan results of this study showed an increase in the interest and skills ofÂ storytelling puppets in Class VI SDN Pangonan 02 on learning the Java language usingprops puppets, from the initial conditions prior to action by the students who told puppetby 27%, following the actions of the first cycle to 55%, and after the second cycleincreased to 100%. While the puppet storytelling skills of the initial conditions beforethe action by 27%, following the actions of the first cycle to 45%, and after the secondcycle increased to 100% .From the discussion of the results of this study concluded thatthe use of props shadow play can increase the interest and skills of storytelling puppet inclass VI SDN Pangonan 02 in the school year 2015/2016.Keywords: interests, skills, storytelling, shadow play props.Â